Capture the missing: formation of (PbBi3)− and [AuPb5Bi3]24− via atom exchange or reorganization of the pseudo‐tetrahedral Zintl anion (Pb2Bi2)2−. Issue 3 (25th May 2022) - Pan, Fuxing; Guggolz, Lukas; Dehnen, Stefanie
Abstract: ( Pseudo‐ )tetrahedral p‐block atom units have been attracting the interest of many scientists, mainly regarding their use as elegant starting materials for compounds with larger molecular or extended architectures. The isoelectronic four‐atomic species that were addressed so far span the range from neutral P4, As4, and AsP3, via the homoatomic Si4 4− anion and its heavier congeners, to heteroatomic Zintl anions (TrPn3 ) 2− or (Tt2 Pn2 ) 2− (Tr = Ga, In, Tl; Tt = Si, Ge, Sn, Pb; Pn = P, As, Sb, Bi). Hence, (Pb2 Bi2 ) 2− in the salt [K(crypt‐222)]2 (Pb2 Bi2 )·en (en = ethane‐1, 2‐diamine) is isoelectronic and isostructural to white phosphorus, but it exhibits significantly different properties owing to its charge and the different nature of the involved atoms, which affects its stability and reactivity. The recently reported compound [K(crypt‐222)]3 [Auη 2 ‐(Pb2 Bi2 )2 ] (A ), isolated from reactions of the binary anion with [AuMePPh3 ] in en, possesses two intact pseudo ‐tetrahedral (Pb2 Bi2 ) 2− moieties. In this work, however, the same reaction of [AuMePPh3 ] with [K(crypt‐222)]2 (Pb2 Bi2 )·en in pyridine instead of en, and subsequent layering with tetrahydrofuran or toluene, yielded two compounds comprising Zintl anions that have not yet been reported to occur in condensed phase. One of them is the (PbBi3 ) − anion, which crystallizes in the triple salt [K(crypt‐222)]4 [(PbBi3 )(Pb2 Bi2 )(AuMe2 )]·6py (1 ). The second is the Pb/Bi moiety in the cluster anion [AuPb5 Bi3 ]2 4−, which was obtained in the compound [K(crypt‐222)]4 [AuPb5 Bi3 ]2 ·2py (2 ). Density functional theory calculations confirm that the (PbBi3 ) − monoanion results from an atom exchange reaction whereas [AuPb5 Bi3 ]2 4− was formed upon more significant reorganization of the reactant (Pb2 Bi2 ) 2− in the presence of Au(I) ions. The trimetallic cluster is the yet missing, heaviest homolog of a series of isostructural species. The new compounds were accessed by a careful selection of the solvent mixtures used for crystallization, which demonstrates the importance of a thorough control of the reaction space. Key Points: Reactions of ( pseudo ‐)tetrahedral anions of p‐block (semi‐)metals with transition metal compounds were proven to be a very versatile access of larger multimetallic clusters; we report on the formation and isolation of two predicted, yet so far elusive, species of both types of heterometallic molecules, (PbBi3 ) − and [(Au2 Pb5 Bi3 )] 4− . By means of computational studies applying high‐level density functional theory (DFT) methods, we were able to rationalize the formation of the uncommon anion (PbBi3 ) −, which is the first monoanionic ( pseudo ‐)tetrahedral molecule. This study confirms both the need and usefulness of DFT calculations in cluster chemistry. Bi‐ or trimetallic cluster compounds may serve as starting materials for new intermetallic phases or act as reactive species in solution or in the gas phase for bond activation themselves. Hence, the understanding of their formation and access on the one hand, and the expansion of the elemental combinations contribute to reach such goals for materials science. Abstract : Reactions of [K(crypt‐222)]2 (Pb2 Bi2 )·en with [AuMePPh3 ] under different solvent/layering conditions afforded different binary or ternary Zintl anions based on either the unchanged (Pb2 Bi2 ) 2− anion, on the unprecedented (PbBi3 ) − anion upon atom exchange, or on complete rearrangement of the starting material to form a larger cluster structure. The compounds were structurally characterized by means of X‐ray diffraction, and their formation and bonding was rationalized by DFT calculations.